Cordyceps militaris extracts inhibit FLT3 protein expression and induce cell cycle arrest in FLT3 overexpressing leukemic cell models - Lae Aung, Win; Chaiyana, Wantida; Chiampanichayakul, Sawitree; Anuchapreeda, Songyot; Tima, Singkome (Journal of Associated Medical Sciences, 2023)
Background: Leukemia is a type of blood cancer, which is characterized by the clonal proliferation of malignant leukocytes resulting in production of abnormal blood cells. Mutations in the FMS-like tyrosine kinase 3 (FLT3) gene are one of the most frequently identified genetic alterations that affect downstream intracellular signaling pathways thereby enhancing leukemogenesis. Nowadays, drugs from herbal sources were selected as alternative drugs for studying their effectiveness on leukemia treatment. Objectives: This study aimed to evaluate anti-leukemia activities of various Cordyceps militaris (C. militaris) extracts including crude extract (Crude) and fractional extracts from hexane (Hex), ethyl acetate (EtOAc), and ethanol (EtOH) on EoL-1 and MV4-11 cells. Materials and methods: Cytotoxicity and effects on FLT3 protein expression and cell cycle progression were investigated and compared with standard cordycepin using MTT assay, Western blotting, and PI staining, respectively. Results: The results demonstrated that EtOAc and Hex fractional extracts showed the strongest cytotoxic effects on EoL-1 cells with inhibitory concentration at 50% growth (IC50) values of 11.0±2.9 and 11.7±0.6 μg/mL and 45.9±0.4 and 36.8±15.3 μg/mL for MV4-11 cells, respectively. Crude and EtOAc fractional extracts exhibited excellent inhibitory effects on FLT3 protein expression. Moreover, the cell cycle progression of both leukemic cells was arrested at S phase after treatment. The obtained results are in the same pattern with standard cordycepin. Conclusion: Overall, this present study showed that anti-leukemia activities of C. militaris on EoL-1 and MV4-11 may involve the inhibition of cell proliferation by inhibiting FLT3 protein expression and inducing cell cycle arrest at S phase and cordycepin may plays a major role of these activities.